Gastric tumor mimicking bronchial tissue associated with a laryngotracheoesophageal cleft: a case report - Erika Nakatani; Keita Terui; Mitsuyuki Nakata; Shugo Komatsu; Ryohei Shibata; Satoru Oita; Yunosuke Kawaguchi; Ayako Takenouchi; Sakurako Harada-Kagitani; Takashi Kishimoto; Koji Fukumoto; Tomoro Hishiki (Surgical Case Reports, 2023)
Abstract Background Laryngotracheoesophageal cleft (LTEC) is a rare disease in which the larynx and trachea communicate posteriorly to the esophagus. It is often associated with other congenital malformations, particularly gastrointestinal anomalies. Herein, we report a case of LTEC associated with a gastric polypoid lesion in bronchial tissue. Case presentation A gastric mass was detected in a male fetus since week 21 of gestation using fetal ultrasonography. Esophagogastroduodenoscopy performed after birth revealed a pedunculated polypoid lesion of the gastric fornix. The patient experienced frequent vomiting and aspiration pneumonia, which persisted after nasoduodenal tube feeding. Communication between the airway and esophagus was suspected. Laryngoscopy performed 30 days later revealed an LTEC (type III). Partial gastrectomy was performed when the patient was 93 days of age. Histopathological examination revealed tumor consisting of cartilage tissue covered with a layer of respiratory epithelium. Conclusion The gastric tumor associated with LTEC exhibited structures mimicking bronchial tissue. LTEC occurs because of foregut maldevelopment, and the tumorous respiratory tissue in the stomach may have been formed from the same abnormal foregut development event as LTEC.